2019
DOI: 10.1002/slct.201900217
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Interaction between New Indole Amide Compound and Aluminum(III) Ion

Abstract: A new indole-based compound N-(pyridine-2-ylmethyl)-1Hindole-2-carboxamide (FL) which could selectively recognize Al 3 + had been designed, synthesized and evaluated. FL could detect Al 3 + with high sensitivity. The fluorescence intensity of FL-Al 3 + solution was linear dependence to the concentration of Al 3 + in the ranges from 0 to 5 μmol/L. The addition of Al 3 + caused quenching of fluorescence intensity and the limit of detection for Al 3 + was as low as 1.79 × 10 À 9 M. The binding ratio of FL-Al 3 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…To rationalize the latter, a systematic comparison of the binding/sensing parameters with previously reported trivalent metal ions responsive optical probes has been recapped (see Table 1). The comparison clearly suggested that the indole‐based probe InNS has an improved LoD value; [68,69] however, the binding constant ( K b ) was comparable ranging from 10 5 to 10 6 M −1 in several cases [70,71] . Notably, the addition of group IIIA and Fe 3+ metal ions induced a significant red‐shift ( ca .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To rationalize the latter, a systematic comparison of the binding/sensing parameters with previously reported trivalent metal ions responsive optical probes has been recapped (see Table 1). The comparison clearly suggested that the indole‐based probe InNS has an improved LoD value; [68,69] however, the binding constant ( K b ) was comparable ranging from 10 5 to 10 6 M −1 in several cases [70,71] . Notably, the addition of group IIIA and Fe 3+ metal ions induced a significant red‐shift ( ca .…”
Section: Resultsmentioning
confidence: 98%
“…The comparison clearly suggested that the indole-based probe InNS has an improved LoD value; [68,69] however, the binding constant (K b ) was comparable ranging from 10 5 to 10 6 M À 1 in several cases. [70,71] Notably, the addition of group IIIA and Fe 3 + metal ions induced a significant red-shift (ca. 70 nm) in the probe InNS in comparison to other reported probes often displaying slightly shifted absorptions.…”
Section: Selectivity Studies Using Uv-vis/fluorescence Analysesmentioning
confidence: 99%
“…Therefore, this was the task of the present document. Thousands of ion-detective fluorescent sensors for ion have been reported upon in the literature ( Zhang et al, 2018 ; Chen et al, 2019 ; Kan et al, 2020 ; Li et al, 2021 ). Importantly, the most common theme in these studies is that the fluorescent molecules investigated were often formed synthetically and their workup often included use of toxic reagents and solvents.…”
Section: Introductionmentioning
confidence: 99%